“One pot" Microwave assisted syntbesis of 5,lO,15-Tri(4- Metboxypbenyl)-20-(4-Cbloropbentyl)-21H,23H-Porpbyrin and its Zinc (TI) Complex. - Loredo Calderón, Erika Lilián; Martínez Lejia, Carolina; López Cortina, Susana; Jiménez Pérez, Víctor Manuel; Hernández Fernández, Eugenio; Cuevas Yañez, Erick (2012)
The syntbesis of new unsymmetrical A,B porphyrin. 5,lO,15-tri(4-methoxypheoy1)-20-(4-chloropheoy1)-21H, 23H-porphyrin. 1. and its Zinc(ll) comp1ex, 5,1 O,15-tri( 4-methoxypheoy1)-20-( 4-ch1oropheoy1)-21, 23- Zinc(II)-pmphine, 2, was accomplished using botb conveotional and "one pot' solventless microwave assisted methods with interesting comparative results. The obtained molecules were characterized by H NMR, UV-Vis and MS. These molecules are considered to represent new compounds with potential application as pbotosensitizers in photodynamic thempy.